Postoperative doxycycline after endoscopic sinus surgery for chronic rhinosinusitis: systematic review with quantitative synthesis - Alshdokhi, Ali M.; Alshahrani, Mubarak A.; Alharbi, Shahd J. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
The antibiotics are commonly and frequently prescribed after endoscopic sinus surgery to treat chronic sinusitis, although their clinical benefit remains uncertain. One such antibiotic, doxycycline, has antimicrobial and anti-inflammatory properties, which improve postoperative recovery. However, recent reviews of infectious complications after endoscopic sinus surgery suggest the importance of antibiotic use, but routine postoperative antibiotic use remains controversial. The study aims to assess whether postoperative systemic doxycycline improves symptoms, endoscopic healing, complications, or microbiome recovery after endoscopic sinus surgery (ESS) for chronic rhinosinusitis (CRS). A PRISMA 2020-oriented systematic review with quantitative synthesis was conducted. The randomized or quasi-randomized adult studies comparing postoperative doxycycline versus placebo/standard care. The searches were performed in MEDLINE (PubMed), Embase, CENTRAL, and Scopus. The results show that of the 247 records screened, two randomized, double-blind, controlled trials met the inclusion criteria. Both evaluated doxycycline (100 mg for 28 days versus placebo) compared to placebo after esophagoscopy in adults with chronic atrophic rhinitis (with or without nasal polyps). Endoscopy and microbiome findings showed no sustained benefit with doxycycline. Side effects were rare and similar between groups. The certainty of the evidence ranged from low to moderate for all outcomes. The authors concluded that the current randomized evidence does not support a symptomatic or endoscopic advantage of postoperative doxycycline after ESS for CRS. While generally safe, its routine use cannot be justified given low-certainty evidence and the importance of antibiotic stewardship. Larger, well-powered trials with standardized outcomes are needed to clarify its role.